Essential Mineral Elements and Potentially Toxic Elements in Orange-Fleshed Sweet Potato Cultivated in Northern Ethiopia - Lamaro, Gloria Peace; Tsehaye, Yemane; Atkilt, Girma; Andrea, Vannini; Riccardo, Fedeli; Stefano, Loppi (Biology, 2023)
This study investigated the influence of the agro-climatic environment of Northern Ethiopia on the content of essential mineral elements of selected orange-fleshed sweetpotato genotypes, the potential contribution of each genotype’s essential mineral elements to the recommended dietary allowance, and the potential risk to human health from the accumulation of potentially toxic elements in the tuberous roots of the studied genotypes. The results showed consistent interspecific variations in the content of essential mineral elements among the studied orange-fleshed sweetpotato genotypes, as well as important intraspecific differences, which could depend on the variations in soil mineral and organic matter content, rainfall, temperature, as well as interactions between genotype and environment. The investigated genotypes, especially Kulfo, Ininda, Gloria, and Amelia, can provide an amount of several essential mineral elements high enough to meet 100% of the recommended dietary allowance for all age groups ≤8 years. The mean content of potentially toxic elements in tuberous roots and their daily intake values were within the recommended permissible levels; likewise, no health risk was associated with the consumption of these genotypes for Cr, As, and Pb. However, Al, Cd, Cu, Fe, Mn, and Ni is > 1, consumption imposes health risks based on daily accumulation.